Purpose and cause in Pauline exegesis: Romans 1.16-4.25 and a new approach to the letters - Dabourne, Wendy (Society for New Testament Studies monograph series, 1999)
Three factors prompt this re-examination of the underlying questions that shape mainstream exegesis of Paul's letters. Hermeneutical studies have destabilized assumptions about the nature of meaning in texts; the letters are usually characterized as pastoral but explicated as expressions of Paul's thought; and the impact of E. P. Sanders' work on Paul has sharpened exegetical problems in Romans 1.16-4.25. The outcome is a two-step method of exegesis that considers a letter first in the light of the author's purpose in creating it and second as evidence for the patterns of thought from which it sprang. The passage appears as pastoral preaching, helping the Romans to deal with the implications of the fact that the God of Israel is now accepting believing Gentiles on the same basis as believing Jews. Justification by grace through faith emerges as the theological understanding of God's action in Christ that grounds pastoral speech.